고도굴곡형 인공 슬관절 전치환술 후 관절운동 - 조세현(Se-Hyun Cho); 하용찬(Yong-Chan Ha); 송해룡(Hae-Ryong Song); 정순택(Soon-Taek Jeong); 박형빈(Hyung-Bin Park); 황선철(Sun-Chul Hwang); 김진수(Jin-Su Kim) (The journal of the Korean Orthopaedic Association, 2004)
목 적: 인공 슬관절 치환술에 사용된 고도 굴곡형(LPS-Flex NEXGEN) 인공 관절 전치환술 후 관절 운동에 영향을 끼치는 요인 및 단기 추시 결과에 대하여 전향적 연구를 통하여 분석하였다. 대상 및 방법: 2001년 12월부터 2002년 3월까지 고도굴곡형 인공 관절을 사용하여 인공 슬관절로 전치환술을 시행한 환자 72명 106예 중 최소 2년 이상 추시된 67명(남자: 7명, 여자: 60명) 101예의 슬관절을 대상으로 하였다. 수술 시 평균 연령은 68.4세(범위, 52-77세)이었다. 수술 후 3개월, 6개월, 1년 및 2년에 환자의 관절 운동 범위 회복을 포함한 임상적 평가를 시행하였다. 최종 추시 시, 수술 후 운동범위에 영향을 미칠 수 있는 인자로 수술 전의 굴곡구축과 운동범위, 그리고 키와 몸무게 비교수치(BMI: body mass Index) 등을 검사하였다. 수술 전후의 대퇴-경골 간 내반 변형 및 수술 후 최종 추시한 슬관절 점수와 기능점수, 슬개골 경사도 및 전위정도를 측정하여 수술 후 운동 범위에 미치는 영향을 분석하였다. 결 과: 수술 후 환자의 최종 추시에서 후속 굴곡은 평균 130.8° (범위, 90-150°)였으며, 30예(30%)에서 140° 이상 굴곡되는 완전한 자신의 슬관절 굴곡을 보였다. 편안한 자세에서 양반다리가 가능한 경우는 53명(85예)이었고, 편한 자세로 꿇어 앉을 수 있는 경우는 20명(30예)이었다. 수술 후 관절운동이 120° 미만인 경우는 11예였다. 대부분의 환자는 수술 후 6개월에서 1년까지 자신의 최대 관절 운동 범위를 가지는 것으로 파악되었다. 수술 후 최종 추시상 슬관절 운동에 영향을 미치는 인자는 수술 전 운동 범위가 가장 중요한 요인으로 판단된다. 슬관절 점수는 평균 90점(범위, 80-100점), 슬관절 기능 점수는 91점(범위, 45-100점)으로 평가하였다. 결 론: 고도 굴곡형 인공 관절을 사용한 인공 슬관절 치환술에서 매우 우수한 평균 관절 운동 범위를 보였으며, 관절 운동 범위를 결정하는 것은 환자의 수술 전 관절 운동 범위라 생각된다. Purpose: The aim of this prospective study was to determine which factors are predictive of the post operative range of motion and to evaluate the short-term clinical results after total knee arthroplasty using The Nexgen Legacy Knee LPS-Flex fixed bearing knee system replacement. Materials and Methods: A total of 67 patients (101 knees) were enrolled in this study. 101 knees were operated on using the LPS-Flex fixed bearing knee system replacement. The same surgeon performed the surgery between December 2001 and March 2002. The patients’ ages ranged from 52 to 77 years,with an average of 68.4 years. Preoperatively the factors considered were the age of the patient, gender, the body mass index, the flexion contracture and further flexion possible. The factors considered postoperatively were patellar tilting and displacement, the postoperative knee and functional score, and a varus deformity. The patients were followed up once every 3 month for up to 2 years. Results: At the latest follow-up, the average flexion in this series was 130.8° (range, 90°-150°). Thirty knees could attain more than 140° flexion. Twenty patients could comfortably kneel down. The 53 patients could sit cross-legged. The eleven knees could attain less than 120° of flexion at the final follow-up. There was a significant improvement in flexion at each successive review 12 months after surgery. The most important factor that influenced the range of motion after an arthroplasty was the preoperative range of flexion. The average Knee Society knee score was 90 points (range, 80-100), and the function score was 91 points (range, 45-100). Conclusion: A total knee arthroplasty with LPS-flex showed an excellent range of motion and satisfactory early clinical results. The most important factor that influences the range of motion after an arthroplasty is the preoperative range of flexion. KCI Citation Count: 6